Off-Target Impacts: Tracing Public Participation in Policy Making for Agricultural Biotechnology. (January 2020) - Card, Daniel J.
Drawing on public comments and drafts of an environmental impact statement, this article examines public participation in policy making via the federal Web siteRegulations.gov . Aiming to be our "voice" in federal decision making, Regulations.gov encourages citizens to submit comments on proposed actions. Drawing on Callon, Lascoumes, and Barthe's "hybrid forum, " the author suggests that ethical and effective participatory policy making should be hybrid in scope, inclusion, and agency. While public participation in policy making is commonly positioned as an antidote to the crisis of trust in science, the author argues that such participation gone wrong could have off-target impacts, raising questions about the promise ofRegulations.gov .